The Use of Autobiographical Poetry to Process Trauma, Promote Awareness, and Shift Views on Sexual Violence: Exploring the “Against Our Will” Campaign - Hand, Michelle D. (Violence against women, 2021)
This article explores a televised campaign featuring poetry by survivors of sex trafficking, a growing domestic and international problem resulting in symptoms of posttraumatic stress. An integrative framework, incorporating feminist autobiography theory with trauma theory, empowerment theory, and a strengths perspective, is used to explore these poems and how poetry can be used to address sexual trauma, endorsing the progress of feminism and feminist methodology. Further support is provided through a systematic scoping review of extant research on the use of poetry to address sexual trauma. Implications are offered for researchers, educators, practitioners, and policymakers in this emerging area of study.